Theca Cell INSL3 and Steroids Together Orchestrate the Growing Bovine Antral Follicle - Dai, Yanzhenzi; Ivell, Richard; Anand-Ivell, Ravinder (Frontiers in Physiology, 2017)
Insulin-like peptide 3 (INSL3) and its specific receptor RXFP2 are both expressed by theca interna cells of the growing antral follicle where they form an essential regulatory element in the production of the steroid precursor androstenedione. Using primary cultures of bovine theca cells from the mid follicular phase together with steroid agonists and antagonists we have examined how ovarian steroids modulate INSL3 expression. Transcript analysis shows that these cells express estrogen receptors alpha and beta, androgen and progesterone receptors, besides the orphan nuclear receptors SF1 and nur77. Whereas exogenous androgens have little or no effect, the androgen antagonist bicalutamide stimulates INSL3 production. In contrast, estrogen receptor agonists, as also progesterone, are stimulatory. Importantly, estrogen receptor signalling is convergent with the protein kinase A signalling pathway activated by LH, such that the estrogen receptor antagonist can inhibit the mild stimulatory effect of LH, and vice versa the PKA antagonist H89 blocks stimulation by estradiol. A significant finding is that the major steroid metabolite androstenedione appears to act predominantly as an estrogen and not an androgen in this system. Transfection of INSL3 gene promoter-reporter constructs together with various steroid receptor expression plasmids supports these findings and shows that steroid action uses non-classical pathways not requiring canonical steroid-responsive elements in the proximal promoter region. Together, the results indicate that increasing estrogens in the follicular phase stimulate a feedforward loop driving INSL3 signalling and thereby promoting steroidogenesis in the growing antral follicle until the LH surge which effectively switches off INSL3 expression.